METHODS OF IMPROVING ANALYZERS IN FOOTBALL - Jalaluddin AMIRQULOV (Scholar Express Journal, 2023)
This article describes the types of attacks and their use in football. It is necessary to know how to use different analyzers to increase the efficiency of the player's activity. This primarily concerns the senses of sight and hearing. You need to know how to evaluate them. Such knowledge is necessary when performing special exercises (for example, eliminating gaze control in order to perform motor tasks "without looking").
Keywords: football; technical-tactical; physical strength; speed